Nutritional Status According to Demographic Characteristics of Peruvian Older Adults - José Ander Asenjo Alarcón (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: the population pyramid is presenting a thickening at the top, reflecting a progressive increase in older adults in recent years, a situation that should draw the attention of the different sectors in order to guarantee healthy aging. Objective: to determine the nutritional status according to the demographic characteristics of older adults cared for in health facilities in Peru. Methods: descriptive, cross-sectional and retrospective study, it was developed during July and August 2021, with 99,056 older adults who were treated in all regions of Peru. The nutritional status and demographic characteristics of older adults were obtained from the national open data platform of the Peruvian Ministry of Health. Univariate analysis was performed using absolute and relative frequencies and confidence intervals for proportions at 95 %, and Mann-Whitney U and Kruskall-Wallis H were used for bivariate analysis, with a statistical significance of p < 0.05. Results: the 54.3 % of older adults had a normal nutritional status, of which 49.9 % were women and 61.2 % men, 50.1 % were between 60 and 69 years old, 56.7 % % from 70 to 79 years old and 59.3 % from 80 years old and over, the nutritional status according to sex and age presented statistically significant differences (p = 0.000). Conclusion: more than half of older adults had a normal nutritional status, being more marked in men and in those 80 years of age or older, these differences were statistically significant.